2005
DOI: 10.1038/sj.bjp.0706347
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pathways triggered by the selective FLT‐1‐agonist placental growth factor in vascular smooth muscle cells exposed to hypoxia

Abstract: We have previously shown that hypoxia makes vascular smooth muscle cells (VSMCs) responsive to placental growth factor (PlGF) through the induction of functional fms-like tyrosine kinase (Flt-1) receptors. The aim of this study was to investigate the molecular mechanisms involved in the PlGF effects on proliferation and contraction of VSMCs previously exposed to hypoxia (3% O2). In cultured rat VSMCs exposed to hypoxia, PlGF increased the phosphorylation of protein kinase B (Akt), p38 and STAT3; activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…PlGF enhances the proliferation, migration, and survival of endothelial cells (Ziche et al 1997;Carmeliet et al 2001;Adini et al 2002;Fischer et al 2007;Schmidt et al 2011), although some of these effects remain debated (see below). This cytokine also stimulates proliferation of mesenchymal fibroblasts and regulates the contractile response of mural cells, organized around the endothelium during collateral vessel growth (Yonekura et al 1999;Bellik et al 2005). In addition, PlGF recruits myeloid progenitors to growing sprouts and collateral vessels (Hattori et al 2002;Luttun et al 2002;Pipp et al 2003;Rafii et al 2003;Scholz et al 2003).…”
Section: Plgf: a Pleiotropic Factormentioning
confidence: 99%
“…PlGF enhances the proliferation, migration, and survival of endothelial cells (Ziche et al 1997;Carmeliet et al 2001;Adini et al 2002;Fischer et al 2007;Schmidt et al 2011), although some of these effects remain debated (see below). This cytokine also stimulates proliferation of mesenchymal fibroblasts and regulates the contractile response of mural cells, organized around the endothelium during collateral vessel growth (Yonekura et al 1999;Bellik et al 2005). In addition, PlGF recruits myeloid progenitors to growing sprouts and collateral vessels (Hattori et al 2002;Luttun et al 2002;Pipp et al 2003;Rafii et al 2003;Scholz et al 2003).…”
Section: Plgf: a Pleiotropic Factormentioning
confidence: 99%
“…To date, VEGFR1 remains the elusive member of the VEGFR family. Although the signaling potential of VEGFR1 remains controversial, it has seemed that VEGFR1 plays a role in inducing signaling responses, especially in the cell types that do not express or express low levels of VEGFR2 (4,6). We found that PI3K/Akt signaling mediated by VEGFR1, but not VEGFR2, is involved in E. coli K1 invasion of HBMEC, and our results showed that the expression level of VEGFR1 is higher than that of VEGFR2 in HBMEC.…”
Section: Vol 78 2010 E Coli K1 Exploits Vegfr1 To Invade Endothelimentioning
confidence: 45%
“…51 It is also possible that PGF binding to FLT1 promotes the transphosphorylation of KDR by FLT1 in FLT1/KDR heterodimers to increase VEGF/KDR signaling. 48 Lastly, PGF activation of FLT1 may stimulate vessel formation and maturation indirectly by acting on non-endothelial cell types, for example smooth muscle cells 24,52 or bone marrow derived cells that are recruited to sites of neovascularization. 25,53,54 It is presently debated whether proangiogenic bone marrow derived cells support tumor angiogenesis by differentiating into endothelial cells 55 or by providing perivascular support cells.…”
Section: Vegf Receptor Signaling In Vertebrate Developmentmentioning
confidence: 99%
“…23 Thus, Flt1 is upregulated in vascular smooth muscle cells experiencing hypoxic stress, perhaps to control vascular remodelling or tone. 24 However, further studies are required to fully understand the physiological significance of the transcriptional regulation of FLT1 by hypoxia, and how it may complement the regulation of VEGF by hypoxia. In contrast to Vegfa and Flt1, Kdr has no HIF1A binding sites in its promoter region and is therefore not regulated by hypoxia.…”
Section: Vegf Receptor Signaling In Vertebrate Developmentmentioning
confidence: 99%